2014
DOI: 10.1136/sextrans-2013-051332
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based partner selection and risk for unprotected anal intercourse in sexual encounters among men who have sex with men: a meta-analysis of observational studies

Abstract: Encounters initiated online have elevated odds for entailing UAI and seroadaptive UAI practices. Online-delivered behavioural interventions should address insufficiency of risk-reducing practices involving UAI relative to consistent condom use and promote frequent HIV testing among MSM seeking UAI partners online. http://group.bmj.com/products/journals/instructions-for-authors/licence-forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 56 publications
3
74
0
Order By: Relevance
“…A meta-analysis of studies on Internet-based partner selection conducted between 2002 and 2009 found that condomless anal sex was 75% more likely to be reported among MSM who found their sex partners on the Internet compared with those who met offline. 53 Geosocial networking apps are the latest platforms for partner seeking. The apps that cater to MSM, such as Grindr, Jack'd, Scruff and Krave, connect men to each other based on geographical proximity.…”
Section: Existing and Anticipated Challenges Of The Sti Epidemic In Msmmentioning
confidence: 99%
“…A meta-analysis of studies on Internet-based partner selection conducted between 2002 and 2009 found that condomless anal sex was 75% more likely to be reported among MSM who found their sex partners on the Internet compared with those who met offline. 53 Geosocial networking apps are the latest platforms for partner seeking. The apps that cater to MSM, such as Grindr, Jack'd, Scruff and Krave, connect men to each other based on geographical proximity.…”
Section: Existing and Anticipated Challenges Of The Sti Epidemic In Msmmentioning
confidence: 99%
“…This is important, because MSM who seek sex partners through online platforms are more likely to report engaging in CAI and having multiple sexual partnerships, as well as being less likely to know the HIV status of these partners, compared with those who meet their partners offline. 7,20,26 A meta-analysis of 11 observational studies found the odds of CAI were higher in online-initiated sexual encounters compared with sexual partnerships conducted offline among MSM, suggesting that online platforms make partner identification for CAI easier. 26 This relationship may be explained by the ease in which sexual partners can be identified, especially for those willing to engage in high-risk sexual behaviours like CAI with a partner of unknown HIV-status or unknown viral load suppression status.…”
Section: Increasing Access To Sex Partners During Travel Through Onlimentioning
confidence: 99%
“…7,20,26 A meta-analysis of 11 observational studies found the odds of CAI were higher in online-initiated sexual encounters compared with sexual partnerships conducted offline among MSM, suggesting that online platforms make partner identification for CAI easier. 26 This relationship may be explained by the ease in which sexual partners can be identified, especially for those willing to engage in high-risk sexual behaviours like CAI with a partner of unknown HIV-status or unknown viral load suppression status. Studies conducted in the US and in East and South-East Asia have shown that the elevated HIV risk may not be due to seeking partners online per se, but to the ways in which online social networking platforms provide increased opportunities for engaging in multiple partnerships, larger sexual networks, CAI or concurrent alcohol use during intercourse.…”
Section: Increasing Access To Sex Partners During Travel Through Onlimentioning
confidence: 99%
“…Of these three factors, we highlight the latter, namely that the increasing popularity of Internet cruising for casual sex has raised the hypothesis that associates this medium with so-called high-risk behaviors 3 . MSM who cruise for partners on the Internet report having more encounters without condoms when compared to other MSM 4 . In Spain, young MSM are more likely to practice unsafe sex (73% ≤ 25 years of age versus 57% > 25 years) 5 .…”
Section: Background and Objectivesmentioning
confidence: 99%